EFFECTIVENESS OF CREDIT MANAGEMENT FOR MAINTAINING LIQUIDITY AND INCREASING PROFITABILITY - Sari, Putri Agusta (Jurnal Administrasi Bisnis, 2013)
In credit distribution,  bank has used the principle of 5C. However, the bank is still not optimally apply the whole principle 5C. To achieve an effective credit management then the bank must make improvements in the analysis of credit. Type of research method is descriptive.  This research is used to determine the credit management applied PT. Bank Tabungan Negara ( Persero ) Tbk, includes : Credit application Process, Credit Approval Process, Supervision Credit and redemption Technique, and settlement of Troubled Credit. Finance ratio analysis are liquidity ratio include quick ratio, banking ratio ( asset to loan ratio, cash ratio, loan to deposit ratio) and profitability ratio include gross profit margin, net profit margin, return on equity capital, and return on total assets. The place to study a selected location where the research is PT. bank Tabungan Negara  (persero),Tbk  which is located at Jalan ade Irma suryani 2-4 Malang. In this study data collection methods used to collect the data required as follow documentation,it is a technique of gathering data by viewing and using report and record of the company.The conclusion of analysis result are Cash Ratio is good, Loan to Deposit Ratio ( LDR ) is good,Return on Equity ( ROE ) is good, Return on Asset (ROA) is good, and quick ratio is not good. Keywords: credit management , effectiveness of credit management, liquidity and profitability.